The Application of Discovery Learning Models in Learning to Write Descriptive Texts - Ariyana Ariyana; Enawar Enawar; Intan Sari Ramdhani; Agus Sulaeman (Universitas Bengkulu, 2020)
The purpose of this study was to describe the application of discovery learning models in learning to write descriptive texts. The research method uses descriptive methods. Data collection techniques using observation techniques, test writing descriptive text, and documentation. Data analysis techniques by reducing data, data presentation, data interpretation, conclusions. The results showed that the steps of the discovery learning model in learning to write descriptive texts are to describe topics, ask questions, formulate hypotheses, carry out investigations, conduct observations, organize or analyze, and present the results of investigations. Then, the students' ability to write descriptive text obtained an average value of 76.8 with good criteria after applying the discovery learning model. The learning to write descriptive text is carried out to instill the value of responsibility to students and improve the ability to write text descriptive students based on text, images, and places, so students are not passive.